2023
DOI: 10.1136/bmjopen-2022-065021
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and staffs’ views and experiences of asymptomatic testing on a university campus during the COVID-19 pandemic in Scotland: a mixed methods study

Abstract: ObjectivesTo explore the acceptability of regular asymptomatic testing for SARS-CoV-2 on a university campus using saliva sampling for PCR analysis and the barriers and facilitators to participation.DesignCross-sectional surveys and qualitative semistructured interviews.SettingEdinburgh, Scotland.ParticipantsUniversity staff and students who had registered for the testing programme (TestEd) and provided at least one sample.Results522 participants completed a pilot survey in April 2021 and 1750 completed the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Several early mixedmethods studies in university settings suggested that some subjects receiving a negative result on a recent test indeed felt reassured and thus willing to liberalize their social interactions. [35][36][37][38][39]…”
Section: Discussionmentioning
confidence: 99%
“…Several early mixedmethods studies in university settings suggested that some subjects receiving a negative result on a recent test indeed felt reassured and thus willing to liberalize their social interactions. [35][36][37][38][39]…”
Section: Discussionmentioning
confidence: 99%
“…We draw on 48 interviews with TestEd participants, carried out between May 2021 and February 2022 as part of the wider TestEd project, a collaboration between biomedical, physical, clinical and social scientists along with health economists. The social science team, made up of behavioral scientists, epidemiologists, sociologists and anthropologists, had the primary objective of conducting surveys and interviews to examine the public health aspects of COVID-19 testing, including facilitators and barriers to testing, and adherence with public health guidelines, in particular those surrounding self-isolation (Bauld et al 2023 ). Interviews took place remotely via Microsoft Teams, Zoom, or phone call due to COVID-19 restrictions.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were similarly interested in the success of TestEd in picking up cases (see Bauld et al 2023 ). Some referred to the visual presence of vials at testing booths as suggestive of testing levels and uptake ( Figure 2 ).…”
Section: Testing For ‘Publics’ and ‘Communities’mentioning
confidence: 99%
See 1 more Smart Citation